Three essays on corporate finance - Le, Zhang (2012)
This dissertation contains three essays on corporate finance. The first essay examines the role of government directors (outside directors with past work experience in government agencies) in corporate governance and their effect on firm performance. We find that unlike nongovernment outside directors, government directors on the board are not associated with an increase in CEO turnover-performance sensitivity. Government directors are also more likely to miss board meetings than nongovernment directors, although not when firms have a major trading relationship with the government. Further, compared to firms without government directors, firms with government directors experience weaker annual operating performance and more negative merger announcement returns, but their mergers are less likely to be challenged by antitrust authorities. We also find that announcements of government director appointments are greeted more negatively by investors than those of nongovernment director appointments. However, our results for operating performance and announcement returns are not observed when firms with government directors operate in regulated industries. Our results highlight the ineffectiveness of government directors as monitors and advisors as well as the circumstances under which they add value.